PENDAMPINGAN POSYANDU RW 04 KELURAHAN DEMANGAN DALAM UPAYA MENDUKUNG GIZI OPTIMAL BALITA - Rosmauli Jerimia Fitriani1 Jerimia Fitriani; Laeli Nur Hasanah (Politeknik Negeri Sriwijaya, 2020)
The preparation of MP-ASI must pay attention to the principles of the presentation and development of toddlers to prevent malnutrition. Posyandu is a place to convey this information. As long as the posyandu is not carried out, the weighing of children under five is carried out independently by cadres, not carried out simultaneously on the same day as usual. Assistance for posyandu activities is carried out with home visits according to health protocols and the use of information technology using whatsapp applications. Home visits are carried out by cadres, bringing materials that have been prepared by the servants. Servants provide the results of coordination with a nutritionist on duty at Posyandu RW 4 Kelurahan Demangan.